The Effect of Nanocurcumin in Improvement of Knee Osteoarthritis: A Randomized Clinical Trial - Hashemzadeh, Kamila; Davoudian, Najmeh; Jaafari, Mahmoud R.; Mirfeizi, Zahra (Current Rheumatology Reviews, 2020)
Objective: Osteoarthritis is a degenerative disease of the joints. Non-steroidal antiinflammatory drugs (NSAIDs) are being used for the treatment of osteoarthritis. However, their use is limited due to complications, such as gastrointestinal bleeding. Therefore, it is necessary to find alternative treatments for osteoarthritis. Recently, nanomicelle curcumin has been developed to increase the oral bioavailability of curcumin. The aim of this study was to evaluate the effect of nano curcumin on the alleviation of the symptoms of knee osteoarthritis patients. Methods: In this randomized, double-blind controlled trial, the intervention group was administered 40 mg of nanocurcumin capsule every 12 hours over a period of six weeks, and the control group received the placebo (similar components of nanomicelle curcumin capsules yet without curcumin). In the final analysis, 36 patients in the nanocurcumin group and 35 patients in the placebo group were enrolled. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was filled for patients in their first visit and at the end of six weeks. Differences were statistically significant at P-value < 0.05. Results: There were no significant differences between the two groups regarding gender, age, Kellgren score, and the duration of the disease before the intervention. A significant decrease was observed in the overall score, along with the scores of pain, stiffness and physical activity subscales of the WOMAC questionnaire in patients of the nano curcumin group compared with the placebo group. Conclusion: Nanocurcumin significantly improves the symptoms of osteoarthritis patients.
Keywords: osteoarthritis